BPTF promotes the progression of distinct subtypes of breast cancer and is a therapeutic target - Bezrookove, Vladimir; Khan, Imran A.; Nosrati, Mehdi; Miller, James R.; McAllister, Sean; Dar, Altaf A.; Kashani-Sabet, Mohammed (Frontiers in Oncology, 2022)
Recent studies have assigned an oncogenic role to the chromatin remodeling factor bromodomain PHD finger transcription factor (BPTF). However, little is known about BPTF’s role in breast cancer progression. Here we show that BPTF copy number is gained in 34.1% and separately amplified in 8.2% of a breast cancer tissue cohort. Elevated BPTF copy number was significantly associated with increasing patient age and tumor grade, and observed in both ER-positive and triple-negative (TNBC) breast cancer subtypes. BPTF copy number gain and amplification were also observed in The Cancer Genome Atlas (TCGA) breast cancer cohort. Stable shRNA-mediated silencing of BPTF significantly inhibited cell proliferation and induced apoptosis in TNBC and ER-positive human breast cancer cell lines. BPTF knockdown suppressed signaling through the phosphoinositide 3 kinase (PI3K) pathway, including reduced expression of phosphorylated AKT (Ser473), phosphorylated GSK-β (Ser9), and CCND1. These findings were confirmed following transient BPTF knockdown by a distinct siRNA in TNBC and ER-positive breast cancer cells. Stable suppression of BPTF expression significantly inhibited the in vivo growth of TNBC cells. Conversely, BPTF cDNA overexpression in TNBC and ER-positive breast cancer cells enhanced breast cancer cell proliferation and reduced apoptosis. BPTF targeting with the bromodomain inhibitor bromosporine, alone or in combination with the PI3K pathway inhibitor gedatolisib, produced significant anti-tumor effects against TNBC cells in vitro and in vivo. These studies demonstrate BPTF activation in distinct breast cancer subtypes, identify pathways by which BPTF promotes breast cancer progression, and suggest BPTF as a rational target for breast cancer therapy.